The influence of orthographic depth on early grade students' reading of words and non-words in Sidaama and English - Samrawit Bekele Demissie; Abraha Asfaw Ambaye; Ingvill Krogstad Svanes (College of education, Bahir Dar University, 2024)
The purpose of this study was to analyse word and non-word reading among early-grade students of Sidaama and English, with a specific emphasis on the difference in orthographic depth between the two languages. The research has a convergent mixed methods design applying reading skills tests, interviews with teachers, and classroom observations. The results of the quantitative and qualitative analysis showed that student scores in Sidaama, which has a transparent orthography, indicated greater accuracy in both word and non-word reading compared to English with its deep orthography. Overall, students read words more correctly than non-words in both languages. Especially in English, the scores for non-words were very low. The results from the reading tests suggest that orthographic differences between the two languages caused challenges for the students when decoding words and non-words. The teachers confirmed the influence of these challenges in interviews, and students were observed struggling to read in class.